(untitled) (Revista Innova Educación, 2024)
The article aims to present the design of a methodological strategy for the care of students with special educational needs not associated with disabilities in the rural sector of the city of Manta, at the Ahitana Ponce Santana Fiscal Educational Unit. The methodology was mixed approach, with a descriptive scope and a non-experimental design. The methods used were analysis, synthesis, inductive and deductive reasoning; additionally, interviews and surveys were conducted with a sample of 3 teachers and 84 students corresponding to sections A and B of the 8th year of Basic General Education, respectively. According to the teachers, the main special educational needs not associated with disabilities in the students include learning difficulties, attention deficit and hyperactivity disorder (ADHD), and language or communication disorders. Students show difficulties in understanding and applying concepts, insecurities in self-esteem and academic confidence, as well as difficulties in conflict resolution and decision-making. Therefore, additional support is required, as well as the development of specific strategies to improve the learning process and academic well-being. The conclusion is reached through a methodological strategy that includes activities aimed at initial assessment, design of individualized intervention plans, use of technological resources to enhance learning and attention, teacher training and support, as well as collaboration with families.